Adenosine transmission from hypothalamic tanycytes to AGRP/NPY neurons regulates energy homeostasis - Nayoun Kim; Seolsong Kim; Seokjae Park; Eun-Kyoung Kim (Experimental and Molecular Medicine)
Abstract Tanycytes are a pivotal component of the hypothalamic network that controls energy homeostasis. Despite their importance, the regulatory mechanisms governing tanycyte–neuron interactions in response to metabolic signals remain unexplored. Here we report that adenosine signaling between tanycytes and AGRP/NPY neurons is crucial for tanycytic metabolic regulation mediated by translocator protein 18 kDa (TSPO). Tanycyte-specific Tspo-knockout mice displayed reduced food consumption and weight loss associated with the downregulation of Agrp and Npy expression under high-fat diet feeding. Tspo-deficient tanycytes had elevated levels of intracellular ATP, which was released via connexin 43 hemichannels and extracellularly converted into adenosine by tanycytic ectonucleotidases. The adenosine signal was perceived by adenosine A1 receptors on adjacent AGRP/NPY neurons, reducing ERK phosphorylation, which in turn downregulated Agrp and Npy expression. Our findings underscore the anorexic role of adenosine as a gliotransmitter in the intricate communication between tanycytes and neurons for regulating appetite and body weight.